2000
DOI: 10.1002/(sici)1520-6866(2000)20:1<11::aid-tcm2>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iron salts and haemosiderin from a thalassaemia patient on oxygen radical damage as measured in the comet assay

Abstract: Thalassaemia is a group of genetic diseases where haemoglobin synthesis is impaired. This chronic anaemia leads to increased dietary iron absorption, which develops into iron overload pathology. Treatment through regular transfusions increases oxygen capacity but also provides iron through the red cells' haemoglobin. An essential treatment, in parallel with transfusions, is the use of chelating agents to remove the excess iron deposited in tissues. These deposits are found in the liver, spleen, heart, and panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…The excess iron deposits in the liver, spleen, heart, pancreas etc, and results in organ failure. Iron chelation is therefore an essential treatment, particularly for polytransfused patients (43). Excess iron has also been described in the thalassemic RBC itself, probably due to increased uptake and/or exposure of the heme moiety due to instability of abnormal hemoglobin molecules (44), such as the ␣-globin tetrameres in ␤-thalassemia (19,24).…”
Section: Fig 2 Flow Cytometric Measurement Of Glutathione (Gsh) Conmentioning
confidence: 99%
“…The excess iron deposits in the liver, spleen, heart, pancreas etc, and results in organ failure. Iron chelation is therefore an essential treatment, particularly for polytransfused patients (43). Excess iron has also been described in the thalassemic RBC itself, probably due to increased uptake and/or exposure of the heme moiety due to instability of abnormal hemoglobin molecules (44), such as the ␣-globin tetrameres in ␤-thalassemia (19,24).…”
Section: Fig 2 Flow Cytometric Measurement Of Glutathione (Gsh) Conmentioning
confidence: 99%
“…28 Hemosiderins isolated from thalassemic patients induced DNA damage in lymphocytes from healthy donors. 29 In the present study, it was also shown that free iron induced oxidative stress in thalassemic lymphocytes, but this effect was not observed for normal lymphocytes (Figure 4). For NTBI to mediate oxidative DNA damage in lymphocytes, it must enter the cells.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies [6,7], it has been shown that lymphocytes from a thalassemia patient were more sensitive to damage from oxygen radicals and iron salts. Because of the Fenton-type chemistry involved, and iron overload that results from dietary absorption, it was considered that, with other dietary agents such as food mutagens and antioxidant flavanoids, the lymphocytes of the thalassemia patient might also show increased sensitivity to the effect of these agents.…”
Section: Introductionmentioning
confidence: 97%